Waddlia chondrophila, a Potential Agent of Human Fetal Death - David Baud; Vincent Thomas; Aliaa Arafa; Lesley Regan; Gilbert Greub (Emerging Infectious Diseases, 2007)
We investigated the zoonotic potential of Waddlia chondrophila, a new Chlamydia-like abortigenic agent in ruminants. Anti-Waddlia antibody reactivity was tested by immunofluorescence and Western blot. Waddlia seroprevalence was higher in women who had had sporadic and recurrent miscarriages than in control women (p<0.001). Waddlia spp. may represent a cause of human fetal loss.